The Role of Mobilizing Teacher Education in Efforts to Improve the Quality of Teacher - Anggraeni, Intan Nur; Rugaiyah, Rugaiyah (Asatiza: Jurnal Pendidikan, 2023)
The quality of teachers tends to decline in this modern era; most teachers need more professionalism to carry out their duties. This is reflected in the low competence of the teacher. The Teacher Competency Test (UKG) conducted on Indonesian teachers showed unsatisfactory results. In addition, the decline in teacher quality can also be caused by several factors, including a lack of knowledge about technology, lack of time discipline, and the negative impact of globalization. The purpose of this study is to provide an understanding that the existence of the Teacher Mobilization Education Program is based on efforts to improve teacher quality. This research uses a qualitative approach with the literature study or literature review method. Data were collected by reviewing the official websites of Google Scholar, Research Gate, sign online and the Ministry of Education Culture Research and Technology of the Republic of Indonesia, with the keyword quality of teacher, teacher competence, teacher and obtained the data about teacher mobilization. The study results a show that teacher mobilization education can help improve the quality of teachers by increasing their competence. Mobilizing teacher education can create active, inclusive, capable, innovative, and sustainable teacher learning habits to support students' learning process. Education is inseparable from the role of the teacher as a role model and leader in learning. This government-initiated program can upgrade the quality of teachers, not only serving as teachers but as trainers and activators for other teachers in the context of developing creative, innovative, and student-centered learning. The driving teacher education program makes teachers more adaptive to the various changes they face with the times. It can cultivate the best learning methods based on existing technology. This study recommends that teachers continue to develop their quality through education and training to face future challenges.